Silver nanoparticles from a gas aggregation nanoparticle source for plasmonic efficiency enhancement in a-Si solar cells. (9th January 2019) - Marom, Sarita; Dorresteijn, Monique; Modi, Ritika; Podestà, Alessandro; Di Vece, Marcel
Abstract: Novel concepts for light management in solar cells are very promising to increase the energy conversion yield, but industrial implementation has been slow. The nanoscale light management techniques often use methods, such as lithography or extensive heating, which are not compatible with industrial requirements. In this work we demonstrate that the use of a gas aggregation nanoparticle source is very suitable to produce optical nanostructures which can enhance the light absorption in a-Si layers. The ultra-clean silver nanoparticles were deposited within a minute at room temperature and their size combined with dielectric environment resulted in increased optical absorption in the near infra-red, where there is room for optical improvement. A thorough transmission electron microscopy and atomic force microscopy analysis provides parameters which are useful for industrial applications. Finite difference time domain (FDTD) simulations confirmed that the experimental optical effects were indeed produced by the plasmonic effect of the silver nanoparticles. These results provide an understanding of how solar cells can benefit from plasmonic nanoparticles from a gas aggregation nanoparticle source.